If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7b-9b-b=9
We move all terms to the left:
7b-9b-b-(9)=0
We add all the numbers together, and all the variables
-3b-9=0
We move all terms containing b to the left, all other terms to the right
-3b=9
b=9/-3
b=-3
| 4r+15r=-19 | | 4h-4h+2h=16 | | 2y=−8 | | -2(x+5)=18 | | 11z-3z+4z-8z=20 | | 11z−3z+4z−8z=20 | | 13r−11r=12 | | 7z+z=8 | | 5x-x/2=4 | | x^2-3x-18.2=0 | | 6d−2/11=2d−2/13 | | 42/60=x/100 | | 6d−2/11=2d−213 | | 6^4x=50 | | 4x(6-2)-5=25 | | -3x-45=-7(x+3) | | 43/60=x/100 | | 10a^2+5a-1=0 | | -5t/2=14 | | 2u=64 | | 72/100=x/60 | | 74/100=x/60 | | 4^8x=33 | | 120+6y=180 | | 73/100=x/60 | | 4x*x=10 | | 10s-4=-69 | | 11x-12=13+10,5x | | 3(4-2x)=6 | | 2x=5(2x+3)=-21 | | m=12=24 | | √8x-21=√18-5x |